Gene Expression Profiling with DNA Microarrays: Advancing Our Understanding of Psychiatric Disorders - Pongrac, Julie; Middleton, Frank A.; Lewis, David A.; Levitt, Pat; Mirnics, Károly (Neurochemical research, 2002)
DNA microarray transcriptome profiling of the postmortem brain opens novel horizons in understanding molecular changes associated with complex psychiatric disorders. With careful analysis and interpretation of microarray data we are uncovering previously unknown, expression patterns that maybe subject-specific and pivotal in understanding the disease process. In our recent studies, analyses of the prefrontal cortex of subjects with schizophrenia and matched controls uncovered complex changes in the expression of genes related to presynaptic secretory release, GABAergic and glutamatergic transmission, metabolic pathways, myelination, as well as cAMP and phosphoinositol second messenger systems. Our goal will be to integrate this expression data within the context of the relevant anatomical, biochemical, molecular, imaging and clinical findings.